PENERAPAN METODE THAWĀB DAN ‘IQĀB DALAM MEMBENTUK AKHLAK SISWA DI SEKOLAH DASAR ACEH BESAR - Yunidar Yunidar (Universitas Islam Negeri Ar-Raniry, 2016)
This study examines the application of the thawÄb and 'iqÄb methods in forming the character of students in Islamic elementary school in Aceh Besar. ThawÄb and 'iqÄb are methods done by giving reward (thawÄb ) on learners who are excellent or well behaved and punishment (' iqÄb) for those who violate the rules or do not behave well. In applying the method thawÄb and 'iqÄb in this educational program, problems arises between them those are which method should comes first and which should be mostly given to children as well as which one is more effective in forming the character of students. The results showed that: 1) the forms of applied thawÄb are material and immaterial things. The method forms 'iqab which is applied in Islamic elementary School in Aceh Besar is in form of 'iqab with cues, 'iqÄb with words, as well as 'iqab with deeds or action.2) Among the methods thawÄb and 'iqÄb, more effective method in forming the character of students is thawÄb method because of its influence on student character changes more durable than the application of' iqÄb. Regarding which method is more effective, it cannot be determined certainly, because every child needs a different treatment. However, in general it can be concluded that in Islamic elementary school in Aceh Besar thawab method used more dominant it can seen from the attitude of the educators were more put thawÄb method of the 'iqÄb. 3) The obstacle faced in applying thawÄb is related to financial. It need more money when the goods is quite expensive. Whereas the obstacle faced in the applying 'iqab is generally associated with fears of a disagreement with a parent about giving 'iqÄb applied in schools.